Electrochemical formation of Fe-V (O) and mechanism of its reaction with water during O-O bond formation - Pattanayak, Santanu; Chowdhury, Debarati Roy; Garai, Bikash; Singh, Kundan K.; Paul, Amit; Dhar, Basab B.; Sen Gupta, Sayam (Chemistry-A European Journal, 2017)
A detailed electrochemical investigation of a series of iron complexes (biuret-modified tetraamido iron macrocycles FeIII-bTAML), including the first electrochemical generation of Fe-V(O), and demonstration of their efficacy as homogeneous catalysts for electrochemical water oxidation (WO) in aqueous medium are reported. Spectroelectrochemical and mass spectral studies indicated FeV(O) as the active oxidant, formed due to two redox transitions, which were assigned as Fe-IV(O)/Fe-III(OH2)and Fe-V(O)/Fe-IV(O). The spectral properties of both of these high-valent iron oxo species perfectly match those of their chemically synthesised versions, which were thoroughly characterised by several spectroscopic techniques. The O-O bond-formation step occurs by nucleophilic attack of H2O on FeV(O). A kinetic isotope effect of 3.2 indicates an atom-proton transfer (APT) mechanism. The reaction of chemically synthesised Fe-V(O) in CH3CN and water was directly probed by electrochemistry and was found to be first-order in water. The pK(a) value of the buffer base plays a critical role in the rate-determining step by increasing the reaction rate several-fold. The electronic effect on redox potential, WO rates, and onset overpotential was studied by employing a series of iron complexes. The catalytic activity was enhanced by the presence of electron-withdrawing groups on the bTAML framework. Changing the substituents from OMe to NO2 resulted in an eightfold increase in reaction rate, while the overpotential increased threefold.